Do we need Complex Systems Science? - Louçã, Jorge (2022 PhDCS Doctoral Workshop - The future of Complex Systems Science, 2022)
The scientific community has embraced the core idea, the vocabulary, and the definition of Complex Systems Science (CSS). However, as can be seen by glancing at its annual conference, the corpus of its research has changed over the last few years. Although the domain's fundamentals are sound, the community is now focused on using CSS to address global issues like the financial and health crises. In this talk, I'll go over the reasons CSS may be used to address worldwide problems by bringing together a variety of knowledge domains and new tools. Additionally, I'll make the case that we must move past simplistic interdisciplinary approaches like those saw during the COVID crisis. I'll conclude by providing examples of problems that can be faced by CSS.